2020
DOI: 10.31729/jnma.4841
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Pre-Anesthetic Medications for Major Surgical Procedures at a Tertiary Care Center: A Descriptive Cross-sectional Study

Abstract: Introduction: Drug utilization research is an important tool to analyze the use of drugs with specialemphasis on medical, social, and economic consequences in society. This study aims to find out theutilization of pre-anesthetic medications in a major surgical procedure. Methods: A descriptive cross-sectional study was conducted from 15th April - 15th August 2019 inthe postoperative ward at Birat Medical College and Teaching Hospital. The convenience samplingmethod was used after ethical clearance from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This finding is in congruent with the findings of study by Shah et al 2020, where majority of population were of female gender (61.8%) and between the age group of 25-39 years of age (53.8%). 7 Also similar results were found as per the retrospective study done by Gajjala et al in 2019. 8 However, it differ from the findings reported by Kulkarni et al in 2017, where most of the patients were of male gender and mean age group was found to be 42.36 years.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding is in congruent with the findings of study by Shah et al 2020, where majority of population were of female gender (61.8%) and between the age group of 25-39 years of age (53.8%). 7 Also similar results were found as per the retrospective study done by Gajjala et al in 2019. 8 However, it differ from the findings reported by Kulkarni et al in 2017, where most of the patients were of male gender and mean age group was found to be 42.36 years.…”
Section: Discussionsupporting
confidence: 85%
“…19 The study conducted by Shah R et al (2020) reported that all patients except children received midazolam and pethidine followed by glycopyrrolate (88%), ondansetron (69%) and others (ketorolac and buscopan, 14.2%). 7 But Oral premedication with 0.5 mg of alprazolam decreases anxiety to the same extent as 7.5 mg of oral midazolam. In majority of patients, alprazolam was found to be as effective as midazolam for anxiety reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Both groups received the usual pre-anaesthetic medications. 12 In addition to routine pre-anaesthetic medications, Group-A received 1 g/kg of Dexmede-tomidine as an intravenous (IV) infusion, while Group-B received an intravenous 2 g/kg of Fentanyl. 13,14 Heart rate and mean arterial pressure were measured in both groups at baseline, 2, and 10 minutes after the intubation.…”
Section: Methodsmentioning
confidence: 99%
“…9 Many studies have shown a lower incidence of postoperative N/V with intravenous midazolam before surgery is finished, as compared to giving it after operation. 10,11,12 We aimed to determine if a sub hypnotic dosage of midazolam, according to a Delphi-study based international expert consensus report, 13 during elective CS under SA affects intraoperative nausea and vomiting.…”
Section: Introductionmentioning
confidence: 99%